Targeted True Lumen Re-Entry With the Outback Catheter: Accuracy, Success, and Complications in 100 Peripheral Chronic Total Occlusions and Systematic Review of the Literature. (August 2015) - Kitrou, Panagiotis; Parthipun, Aneeta; Diamantopoulos, Athanasios; Paraskevopoulos, Ioannis; Karunanithy, Narayan; Katsanos, Konstantinos
Purpose: To report a single-center experience with the Outback re-entry device for targeted distal true lumen re-entry during subintimal recanalization of chronic total occlusions (CTOs) and compare the results with a systematic review of the literature.Methods: Between February 2011 and July 2013, 104 Outback devices were employed in 91 patients (mean age 64±9 years; 57 men) for subintimal recanalization of 100 vessels with CTOs after initial failure of spontaneous reentry. Fifty-two cases involved a retrograde approach to aortoiliac occlusions and 48 were re-entry attempts in infrainguinal CTOs. Outcome measures included complications and technical success, defined as successful targeted re-entry at the preplanned site of the distal true lumen. To evaluate device accuracy, the re-entry distance (between the point of true vessel reconstitution and the eventual re-entry point) was measured.Results: Outback success was 93% (93/100); only 7 cases failed owing to heavy calcification (5/52 aortoiliac vs 2/48 infrainguinal, p=0.44). Re-entry was highly accurate, with a re-entry distance of ~1 cm in both subgroups (1.2±0.1 cm in aortoiliac vs 1.3±0.1 cm in infrainguinal, p=0.40). There were no major and 17 minor complications (9/52 aortoiliac vs 8/48 infrainguinal, p=0.93). Results are in line with the systematic review that identified 11 studies (only 1 randomized trial) involving mostly the femoropopliteal segment (119 aortoiliac and 464 infrainguinal segments). The pooled Outback success rate was 90% (95% confidence interval 85% to 94%) and the pooled complication rate was 4.3% (95% confidence interval 1.6% to 8.3%).Conclusion: The Outback device is safe and has a very high rate of achieving targeted true lumen re-entry, which minimizes the sacrifice of healthy vessel in the aortoiliac and infrainguinal arteries.